Rediscovery of a fossil dolichoderine ant lineage (Hymenoptera: Formicidae: Dolichoderinae) and a description of a new genus from South America - Wild, Alexander (2006)
We describe a new genus, Gracilidris Wild & Cuezzo gen. nov., and a new species, G. p o mb e r oGracilidris Wild & Cuezzo gen. nov., and a new species, G. p o mb e r o Wild and Cuezzo sp. nov., of dolichoderine ants (Hymenoptera: Formicidae: Dolichoderinae) from Paraguay, Brazil and Argentina based on the worker caste. These ants are morphologically similar to the extinct Gracilidris humilioides (Wilson 1985) comb. nov., known from a single Dominican amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. Paraguay, Brazil and Argentina based on the worker caste. These ants are morphologically similar to the extinct Gracilidris humilioides (Wilson 1985) comb. nov., known from a single Dominican amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. Paraguay, Brazil and Argentina based on the worker caste. These ants are morphologically similar to the extinct Gracilidris humilioides (Wilson 1985) comb. nov., known from a single Dominican amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. Paraguay, Brazil and Argentina based on the worker caste. These ants are morphologically similar to the extinct Gracilidris humilioides (Wilson 1985) comb. nov., known from a single Dominican amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. Paraguay, Brazil and Argentina based on the worker caste. These ants are morphologically similar to the extinct Gracilidris humilioides (Wilson 1985) comb. nov., known from a single Dominican amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. Paraguay, Brazil and Argentina based on the worker caste. These ants are morphologically similar to the extinct Gracilidris humilioides (Wilson 1985) comb. nov., known from a single Dominican amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. Paraguay, Brazil and Argentina based on the worker caste. These ants are morphologically similar to the extinct Gracilidris humilioides (Wilson 1985) comb. nov., known from a single Dominican amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. Paraguay, Brazil and Argentina based on the worker caste. These ants are morphologically similar to the extinct Gracilidris humilioides (Wilson 1985) comb. nov., known from a single Dominican amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. Paraguay, Brazil and Argentina based on the worker caste. These ants are morphologically similar to the extinct Gracilidris humilioides (Wilson 1985) comb. nov., known from a single Dominican amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. sp. nov., of dolichoderine ants (Hymenoptera: Formicidae: Dolichoderinae) from Paraguay, Brazil and Argentina based on the worker caste. These ants are morphologically similar to the extinct Gracilidris humilioides (Wilson 1985) comb. nov., known from a single Dominican amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr. Gracilidris humilioides (Wilson 1985) comb. nov., known from a single Dominican amber fossil, that we redescribe and transfer to Gracilidris from Linepithema Mayr.Gracilidris from Linepithema Mayr.